Cambodia's curse : the modern history of a troubled land - Brinkley, Joel, 1952-2014 (PublicAffairs, 2011)
Nobel Prize winning reporter Joel Brinkley illuminates the country, its people, and the deep historical roots of its modern-day behavior.